The Mediating Role of Customer Service in the Relationship between Price and Internet Speed on Customer Satisfaction - Agung Pujianto (Majalah Ilmiah Bijak, 2025)
Customer satisfaction in internet services is a critical factor in maintaining user loyalty, especially for major service providers like Indihome. Despite offering a wide range of packages with varied prices and internet speeds, Indihome continues to face customer dissatisfaction due to discrepancies between expectations and actual service quality, primarily regarding perceived high prices and inconsistent internet speeds. Additionally, customer service frequently becomes a focal point of complaints, with issues related to delayed responses and inadequate problem-solving, further exacerbating the dissatisfaction when service quality does not meet expectations. This study aims to investigate the impact of pricing and internet speed on customer satisfaction, with customer service functioning as a mediating variable. Adopting a quantitative research approach, this study utilizes a survey method to collect data from Indihome users who have been subscribed for over a year. The data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS-SEM) to evaluate the relationships among variables. The findings indicate that both pricing and internet speed have a significant and positive effect on customer satisfaction, while customer service plays a mediating role that strengthens these relationships. The results highlight the importance of customer service quality in mitigating the negative perceptions associated with high prices and unstable internet speeds. The study contributes to the theoretical understanding of customer satisfaction by incorporating customer service as a mediating factor and offers practical implications for service providers to enhance user experience through improved customer support mechanisms.